(untitled) (Web of Teachers: Inderscience Research, 2026)
This article discusses how podcasts can assist university students and English learners enhance their speaking skills. Podcasts have become an effective tool for language acquisition because they are easy to access, sound natural, and can be used in a variety of ways. The article discusses podcasts and how they can help people improve their English-speaking skills, such as how to say words correctly, speak smoothly, acquire new terms, understand what they hear, and feel more confidence while speaking with others. It also examines real-life instances of what teachers do in the classroom, as well as novel teaching methods that make use of podcasts. The article presents research findings demonstrating that podcasts can help students communicate more effectively. It discusses the negative aspects of utilizing podcasts to teach English. The findings demonstrate that podcasts facilitate learning about the student and allow people to study on their own, which can lower nervousness about speaking. According to the article, podcasts are a learning tool that can assist people improve their English-speaking skills when combined with activities that encourage people to converse.